Oral Presentations Abstracts: ETHICS SUPPORT FOR THE DISTRIBUTION OF HOSPITAL BEDS: CO-CREATING A MAP OF VALUES AND NORMS FOR THE ALLOCATION MEETINGS - DE SNOO-TRIMP, Janine; HARTMAN, Laura; MOLEWIJK, Bert (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Background: Allocating admitted patients to their wards is increasingly put under pressure due to high bed occupancy rates. Consequently, allocation becomes morally challenging as it is confronted with potentially conflicting values like protecting teams’ workload, solidarity between wards and quality of care. Furthermore, there is a continuous uncertainty regarding expected intake, discharge, available beds and personnel. An integrative ethics support project was started to help to better deal with these challenges. After identifying core moral challenges, the aim of the current project was to co-create a map of values and norms for the daily allocation meetings. Methods: This qualitative study included observations of allocation meetings and 13 interviews. Subsequently, in five working group sessions a map of relevant values and norms was co-created with a selection of involved professionals. Results: Findings revealed moral challenges in three so-called ‘moral circles’: 1) one’s own team; 2) the hospital and 3) the hospital’s region. A map was developed including important and agreed upon values with 14 norms for the daily allocation meetings. Additionally, formal policies were updated and a conversation method was introduced to guide discussions when there are moral challenges. Conclusion: The joint development of the map led to a shared and practical product for both discussions and decisions regarding bed allocation. Its development already contributed to increased awareness of and openness about moral challenges. Using the map in daily allocation meetings may further stimulate moral reflection on these challenges to support these healthcare professionals in making well-considered and value-based decisions.